2010
DOI: 10.1177/0894439309335169
|View full text |Cite
|
Sign up to set email alerts
|

Network Hopes

Abstract: In this work, the authors examine four cases of municipalities that have attempted to create municipal-sponsored wireless broadband networks. In each of these cases, one of the reasons given for establishing the network was to engage the citizens in their community and government. In each of these cases, the efforts have failed in some way. This problem rests on several assumptions. First, these municipalities believe in the importance and need to increase civic engagement, public participation in local govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 63 publications
0
4
0
1
Order By: Relevance
“…Recent research has, however, suggested that the influence of technology is complex. Tapia and Ortiz () explored four wireless broadband initiatives as part of a wider 10‐city analysis in the United States, which sought to enhance public participation and tackle wider social problems. Each initiative has been largely ineffective because of the technologically determinist approach adopted by local public officials, who presumed that social benefits would prevail if the infrastructure and support was provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research has, however, suggested that the influence of technology is complex. Tapia and Ortiz () explored four wireless broadband initiatives as part of a wider 10‐city analysis in the United States, which sought to enhance public participation and tackle wider social problems. Each initiative has been largely ineffective because of the technologically determinist approach adopted by local public officials, who presumed that social benefits would prevail if the infrastructure and support was provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scholarship has mostly studied the present of Wi-Fi rather than its past. Wi-Fi networks have been researched in their role of building community networks and “bottom-up infrastructures” ( Crabu and Magaudda, 2017 ; Forlano, 2009 ; Meinrath, 2005 ; Shah and Sandvig, 2008 ); they have been studied through their public dimension ( Hampton and Gupta, 2008 ; Hampton et al, 2010 ; Powell, 2008 ; Tapia and Ortiz, 2010 ) and particular attention has been paid to their license-exempt position in the radio spectrum ( Werbach, 2003 ).…”
Section: Standardization Of Wireless As a Social Constructionmentioning
confidence: 99%
“…In this way Internet infrastructure is run like a public utility. The long-term feasibility of municipal broadband is still unclear as it has had its share of failures (see Tapia and Ortiz, 2010) as well as successes in Chattanooga, Tennessee (Wyatt, 2014) and Lafayette, Louisiana (Jervis, 2012).…”
Section: Market and Non-market Spaces In The Digital Environmentmentioning
confidence: 99%